2020
DOI: 10.1371/journal.ppat.1008311
|View full text |Cite
|
Sign up to set email alerts
|

A live auxotrophic vaccine confers mucosal immunity and protection against lethal pneumonia caused by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is one of the leading causes of nosocomial pneumonia and its associated mortality. Moreover, extensively drug-resistant high-risk clones are globally widespread, presenting a major challenge to the healthcare systems. Despite this, no vaccine is available against this high-concerning pathogen. Here we tested immunogenicity and protective efficacy of an experimental live vaccine against P. aeruginosa pneumonia, consisting of an auxotrophic strain which lacks the key enzyme involved in D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Recently, Cabral et al used a live auxotrophic strain (PAO1∆murI) lacking an enzyme involved in D-glutamate biosynthesis, an essential component of peptidoglycan. Both humoral and cellular responses were triggered when delivered intranasally in a two-dose vaccination schedule, leading to murine survival of 86-88% against lethal pneumonia [190].…”
Section: Whole-cell Killed and Live-attenuated P Aeruginosa Vaccinesmentioning
confidence: 99%
“…Recently, Cabral et al used a live auxotrophic strain (PAO1∆murI) lacking an enzyme involved in D-glutamate biosynthesis, an essential component of peptidoglycan. Both humoral and cellular responses were triggered when delivered intranasally in a two-dose vaccination schedule, leading to murine survival of 86-88% against lethal pneumonia [190].…”
Section: Whole-cell Killed and Live-attenuated P Aeruginosa Vaccinesmentioning
confidence: 99%
“…A randomized clinical trial evaluated recombinant IC43 100 μg vaccination against potentially lethal P. aeruginosa infection in mechanically ventilated non-surgical ICU patients and found that it was both immunogenic and well-tolerated [ 127 ]. A live vaccine containing auxotrophic strain that lacks the key enzyme involved in D-glutamate biosynthesis, a structural component of the bacterial cell wall, confers mucosal immunity and protection against lethal pneumonia caused by P. aeruginosa [ 128 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these cells have been implicated in protective mechanisms against protozoan infections [52,53]. It would therefore be worth determining whether these cells could be mediating the pulmonary protective effect observed in the NcMP/CARB mouse group, since IL-17-mediated responses in the lungs induced by intranasal immunization have been previously associated with host protection from diverse infections [54][55][56][57]. The intranasal immunization used here also induced N. caninum antigen responsive liver leukocyte cells producing IL-17A.…”
Section: Discussionmentioning
confidence: 85%